A Multi-Cultural Study of Salespeople's Behavior In Individual Pay-For-Performance Compensation Systems: When Managers Are More Equal And Less Fair Than Others. Issue 3 (3rd July 2017) - Rouziès, Dominique; Onyemah, Vincent; Iacobucci, Dawn
Abstract : In this research, we examine salespeople's behavior in individual pay-for-performance compensation systems and show how perceived management fairness seems to energize sales employees in some environments but not in others. We use a large multicountry database of individual-level remuneration for more than 2, 500 salespeople across four B2B industry sectors to demonstrate cultural adaptations of the effect of perceived management fairness. The results indicate that top management should be concerned with employees' perceptions of fairness in addition to the more typical concerns of control and motivation widely acknowledged in the microeconomics-based sales-force compensation literature. In particular, we show that perceptions of management fairness are key to salespeople's proportion of total pay generated by pay-for-performance formulas.